Laboratory at Birkbeck College, 1958 - Finch, John (1958)
Black and white photograph of Rosalind Franklin's (1920–1958) laboratory at Birkbeck College, taken shortly after her death.
Keywords: Laboratories; Franklin, Rosalind, 1920-1958; Birkbeck College